Functional Verification of Two Genes Related to Stripe Rust Resistance in the Wheat-Leymus mollis Introgression Line M8664-3 - Jin, Pengfei; Chao, Kaixiang; Li, Juan; Wang, Zihao; Cheng, Peng; Li, Qiang; Wang, Baotong (Frontiers in Plant Science, 2021)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most widespread and destructive fungal diseases of wheat worldwide. The cultivation and growth of resistant wheat varieties are the most economical, effective, and environmental friendly methods to control stripe rust. Therefore, it is necessary to use new resistance genes to breed resistant wheat varieties. A single dominant gene temporarily designated as YrM8664-3, from a wheat-Leymus mollis introgression line M8664-3 highly resistant to Chinese predominant Pst races, is a potentially valuable source of stripe rust resistance for breeding. Herein, based on previous YrM8664-3 chromosome location results (bin 4AL13-0.59-0.66 close to 4AL12-0.43-0.59) and expression change information of candidate genes and bioinformatics analysis, several candidate genes with significantly different expression changes were then selected and verified by virus-induced gene silencing (VIGS). Two of the candidate genes temporarily designated as TaFBN [containing plastid lipid-associated proteins (PAP)_fibrillin domain in its protein] and Ta_Pes_BRCT [containing Pescadillo and breast cancer tumour suppressor protein C-terminus (BRCT) domain in its protein], produced the most significant resistance changes in the wheat-Pst interaction system after silencing. These two genes were further verified by Agrobacterium-mediated wheat genetic transformation technology. According to the identification of disease resistance, the resistance function of the candidate gene TaFBN was further verified. Then, the expression of TaFBN under hormone treatment indicated that TaFBN may be related to the salicylic acid (SA) and abscisic acid (ABA) signaling pathways. Combined with the expression of TaFBN in response to environmental stress stimulation, it can be reasonably speculated that TaFBN plays an important role in the resistance of wheat to Pst and is involved in abiotic stress pathways.